Cooperative breeding shapes post‐fledging survival in an Afrotropical forest bird. Issue 10 (7th April 2017) - Van de Loock, Dries; Strubbe, Diederik; De Neve, Liesbeth; Githiru, Mwangi; Matthysen, Erik; Lens, Luc
Abstract: For avian group living to be evolutionary stable, multiple fitness benefits are expected. Yet, the difficulty of tracking fledglings, and thus estimating their survival rates, limits our knowledge on how such benefits may manifest postfledging. We radio‐tagged breeding females of the Afrotropical cooperatively breeding Placid greenbul ( Phyllastrephus placidus) during nesting. Tracking these females after fledging permitted us to locate juvenile birds, their parents, and any helpers present and to build individual fledgling resighting datasets without incurring mortality costs or causing premature fledging due to handling or transmitter effects. A Bayesian framework was used to infer age‐specific mortality rates in relation to group size, fledging date, maternal condition, and nestling condition. Postfledging survival was positively related to group size, with fledglings raised in groups with four helpers showing nearly 30% higher survival until independence compared with pair‐only offspring, independent of fledging date, maternal condition or nestling condition. Our results demonstrate the importance of studying the early dependency period just after fledging when assessing presumed benefits of cooperative breeding. While studying small, mobile organisms after they leave the nest remains highly challenging, we argue that the telemetric approach proposed here may be a broadly applicable method to obtain unbiased estimates of postfledging survival. Abstract : While avian group living typically accrues multiple benefits, it is yet unknown how these benefits manifest post‐fledging. Here, by using an indirect radio‐telemetry approach, we found that cooperation increases fledgling survival in an Afrotropical forest bird. This result indicates the importance of considering the full breeding cycle in cooperative breeding research, which may ultimately lead to a better understanding of evolutionary drivers of cooperation.